The effect of the decisions of the Constitutional Court of Bosnia and Herzegovina on the changes in the organization of the authorities of the entities and Bosnia and Herzegovina: Has the Constitutional Court realized the role of protector of the constitu - Pilipović, Milan B (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
The Constitutional Court of Bosnia and Herzegovina, with its decisions, influenced significant changes in the constitutional organization of the authorities and entities of Bosnia and Herzegovina. When making decisions, there were diametrically opposed views of the judges, and from the theoretical and legal aspect, the explanations of the majority decision of the court are disputed. By passing the decision on the "constituency of the people" on the entire territory of Bosnia and Herzegovina, the Constitutional Court of Bosnia and Herzegovina influenced significant changes in the constitutional organization of the authorities of the Republika Srpska and the Federation of Bosnia and Herzegovina. The manner in which the aforementioned decision was implemented is contrary to the provisions of the entity Constitutions and the Constitution of BiH, because the amendments were imposed by the High Representative’s decision. The High Representative acted as a constitutional and legislative authority, enacting laws which, against the will of the entities, established new competences and new institutions of Bosnia and Herzegovina and thus revised the Constitution of Bosnia and Herzegovina. Accepting the competence to evaluate the constitutionality of the laws passed by the High Representative for Bosnia and Herzegovina, two decades ago, and even today, the Constitutional Court decided that they were in accordance with the Constitution of Bosnia and Herzegovina, thus giving legality to the activities of the High Representative and the new institutions of Bosnia and Herzegovina, which in There is no Constitution of Bosnia and Herzegovina. Thus, the Constitutional Court, with its decisions, influenced the change in the organization of the government of Bosnia and Herzegovina. The author concludes that the Constitutional Court of Bosnia and Herzegovina has not fulfilled its role as protector of the constitution and organization of the authorities of Bosnia and Herzegovina and the entities